2014
DOI: 10.1039/c3ra47998f
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic aerosol-deposited TiO2 photoelectrodes for photoelectrochemical solar water splitting

Abstract: The supersonically expanded gas flow accelerating titania particles for the fabrication of a titania thin film as a photoelectrochemical anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…It is clear that the photocurrent density increases with film mass. As discussed previously, the thicker films not only absorb more light, but more importantly have more micro‐cracks and pores, and therefore have greater accessible surface area for catalysis . However, using the pure TiO 2 , there was a maximum film thickness to which the kinetic spraying was limited.…”
Section: Resultsmentioning
confidence: 92%
“…It is clear that the photocurrent density increases with film mass. As discussed previously, the thicker films not only absorb more light, but more importantly have more micro‐cracks and pores, and therefore have greater accessible surface area for catalysis . However, using the pure TiO 2 , there was a maximum film thickness to which the kinetic spraying was limited.…”
Section: Resultsmentioning
confidence: 92%
“…Earlier work not based on the cold spraying method revealed that the photoresponse of TiO 2 films fabricated by aerosol deposition depended upon film thickness. The highest photocurrent of 93 µA cm ‐2 was obtained for a film thickness of 4 µm . However, for TiO 2 films irradiated with an electron beam, the PCD increased even more up to 0.205 mA cm ‐2 .…”
Section: Applications Of Supersonic Cold Spraying For Energy and Environmental Technologiesmentioning
confidence: 94%
“…The highest photocurrent of 93 A/cm 2 was obtained for a film thickness of 4 m. [177] However, for TiO 2 films irradiated with an electron beam, the PCD increased even more up to 0.205 mA/cm 2 . [178] Furthermore, to enhance the photocurrent, solution-based aerosol deposition was reported, whereby graphene was added to TiO 2 to reduce the electron-hole recombination and enable faster charge transfer.…”
Section: Photoelectrodes For Photoelectrochemical Water Splittingmentioning
confidence: 99%
“…The accelerated particles are pulverized upon impact with the substrate, forming a thin film. A complete description of the experimental setup is available elsewhere [15][16][17][18][19].…”
Section: Materials Propertiesmentioning
confidence: 99%